Hybridisation effect on operating costs and optimal sizing of components for hybrid electric vehicles. (2017) - Carignano, Mauro G.; Nigro, Norberto M.; Junco, Sergio; Orbaiz, Pedro
Reductions of fuel consumption and gas emissions count among the main advantages of hybrid electric vehicles (HEV). It is well known that the level of hybridisation has a large influence on the fuel consumption, the manufacturing cost and the battery lifetime. Therefore, a proper selection of the size of components could be the result of a trade-off between them. This paper provides models and a methodology to address the sizing of components of a HEV. Specifically the work is focused on the series architecture with internal combustion engine and battery. The sizing criteria are oriented to reduce the operating costs, in which are included the fuel consumption and the battery-life consumption. Finally, the methodology proposed is applied in a case study. It corresponds to a real hybrid electric bus operating under urban driving conditions. Simulation results show that the best solutions are obtained by oversizing the battery with respect to power requirements.